Implementation of message authentication code using DNA-LCG key and a novel hash algorithm - Gurpreet Kour Sodhi; Gurjot Singh Gaba; Lavish Kansal; Mohamed El Bakkali; Faisel Em Tubbal (International Journal of Electrical and Computer Engineering (IJECE), 2019)
With the introduction of electronic form of data, the need for an automatic system of security to protect the integrity of data while being transferred from one place to another is required. This is especially the case for a network in which the systems are accessed over a public network or internet. Security mechanisms involve the use of more than one algorithm. They further require that the participants should possess a secret key, which raises issues about creation, distribution and proper usage of these keys. The most effective technique used in provisioning security is Message Authentication Code (MAC) which helps in preserving integrity. MAC involves the use of secret key along with a hash algorithm. In this paper, we present an implementation of MAC using a secret key created by Deoxyribonucleic Acid (DNA) and random output sequence of Linear Congruential Generator (LCG). The hash algorithm used is made more robust by adding complexity to the traditional SHA-160. The presented scheme RMAC (Robust Message Authentication Code) is tested on National Institute of Science and Technology (NIST) test suite for random numbers, avalanche criteria and resistance towards network attacks. The results reveal that the scheme is efficient and is applicable for a variety of security demanding environments.